Optimization of L-tryptophan and thiotriazoline compound analysis by high-performance liquid chromatography - L. I. Kucherenko; S. A. Borsuk; I. A. Mazur; L. G. Cherkovska; D. Yu. Skoryna (Zaporozhye State Medical University, 2018)
Introduction. An actual task of modern medicine is the development of treatment methods of the central nervous system diseases. The solution of this problem was the creation of new, more effective neuropsychotropic drug that shows pronounced antidepressant, nootropic, neuroprotective and antioxidant effects based on the fixed combination of L-tryptophan with thiotriazoline. One of the steps in creating a new drug is the standardization of active ingredients. Today, much attention is being paid to new physical-chemical methods of drugs study, including high-performance liquid chromatography (HPLC). Increasingly, the HPLC method is used for the determination of active ingredients of organic nature, both in mono-preparations and in combined dosage forms. Therefore, we have proposed the HPLC method for new combined L-tryptophan and thiotriazoline drug in order to determine active substances based on their effects. The purpose of our study is to develop a method for the simultaneous standardization of L-tryptophan and thiotriazoline in an artificial compound by high-performance liquid chromatography, in particular the selection of the mobile and stationary phase. Materials and methods. In the first stage of our work, a selection of phase and eluents was carried out for L-tryptophan and thiotriazoline model compound in a ratio of 1:1. The analysis method of thiotriazoline in the reverse phase (C 18) using the eluents, which are water-methanol compounds, was taken as a basis. Results. In the course of study, it was found that the retention volume of both tryptophan and thiotriazoline decreased, and the peak distribution coefficient increased with the number of theoretical plates with increasing content of methanol in phosphate buffer compound. Therefore, as an eluent, attention was drawn to a solution of 20% methanol with 80 % phosphate buffer. Under these conditions, the tryptophan retention volume was 15.11 ml, thiotriazoline - about 6.05 ml, the efficacy of the chromatographic column, calculated on the tryptophan peak of about 3300 theoretical plates. Findings: A highly sensitive technic was developed as part of the study for the simultaneous determination of L-tryptophan and thiotriazoline in a model mixture by HPLC (high performance liquid chromatography method, that is planned to be used in further study, was developed as a part of the study. The method is developed not only for L-tryptophan and thiotriazoline standardization in the combined drug, but also for their determination in biological fluids.